ISPC Commentary on the Revised Proposal for CRP3.6 - February 2012 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2012)
ISPC Commentary on the revised proposal for CRP3.6: Dryland cereals (Revision of February 2012).